The Ethics of Professional Skepticism: A Study in Indonesia Supreme Audit Institution - Supeni Anggraeni Mapuasari (President University Press, 2017)
This research elaborated the influence of ethics to government’s external auditor professional skepticism. Ethics has been argued as one important variable affecting auditor professional skepticism. Components of ethics being tested in this research are moral reasoning and perceived importance of moral intent. Theory of cognitive dissonance was utilized to operationalize the hypothesis analysis of this research. The respondents of this research are auditors of Indonesian Supreme Audit Institution (SAI). Questionnaries were spread of in the SAI training institution and being analyzed with regression analysis by SPSS. The result of this study found a positive relationship between moral reasoning and auditor professional skepticism. However, it failed to proof the relationship between moral intent and auditor professional skepticism. This result gives a practical and theoritical contribution to the development of auditor skepticism in public sector.